Sengketa Pemilihan Kepala Daerah: Studi Kasus Pemilihan Gubernur di Maluku Utara - Riri Nazriyah (Jurnal Hukum IUS QUIA IUSTUM, 2008)
The direct residential as well as provincial election may pave the way for the enhancement of the quality of democracy. It is unfortunate however, that among those elections have raised the conflict and social unrest, which led to the lack of recognition of the elected candidates, and finally the cases then are brought to the court.  Legal provisions pertaining to the way these disputes shall be settled are also have not yet been synchronized. This brings about that General Election Commission (KPU) as well as Local Election Commission (KPUD) and the Supreme Court (MA) hold their own legal  interpretations which differs each from others.